Effects of quercetin, vitamin E, and estrogen on Metabolic-Related factors in uterus and serum of ovariectomized rat models. (3rd August 2021) - Jafari Khorchani, Majid; Samare-Najaf, Mohammad; Abbasi, Ali; Vakili, Sina; Zal, Fatemeh
Abstract: Aims: Estrogen (E2) deficiency has been related to uterine metabolic dysfunction, which could be accompanied by infertility in the reproductive ages. Despite having adverse effects, estrogen replacement therapy is considered the fundamental treatment strategy for this problem. The current study sought to determine the palliative effects of quercetin (Q) and vitamin E (Vit.E) on some of the uterine's metabolism-related factors in ovariectomized (OVX) rats and compare them with the effects of estrogen. Materials and methods: Sixty-four rats were divided into eight groups. OVX animals were treated with Q (15 mg/kg/day), Vit.E (60 mg/kg/day), E2 (10 µg/kg/day), and Q (7.5 mg/kg/day) + Vit.E (30 mg/kg/day) for 10 weeks. Glucose and adiponectin were measured using glucose oxidase and ELISA, respectively. Furthermore, the present study investigated the alterations in the expression of AdipoR1, nesfatin1, and GluT4 genes. Results: Antioxidants suppress the weight gain of OVX animals. Also, Q, Vit.E, and E2 cause a significant decline in glucose and adiponectin levels ( p -value < .05). Finally, the expression of AdipoR1, nesfatin1, and GLUT4 genes was significantly increased in treated OVX rats' uterus. Conclusion: The present findings suggest that the administration of Q and Vit.E could demonstrate promising characteristics in a similar approach with estradiol and thus be considered as alternatives for estrogen replacement therapy.